A model of identity grounded in the acute season of survivorship. Issue 10 (7th August 2018) - Thiessen, Maclean; Hack, Thomas F.; Pitz, Marshall; Anderson, Marcia
Abstract: Objective: Survivorship literature generally focuses on the cancer experience after diagnosis and treatment. However, acute survivorship, beginning with diagnosis and ending at the completion of treatment, has a lasting impact on the well‐being of patients. The purpose of this study was to generate a theoretical understanding of how identity is affected during acute survivorship. Methods: Using grounded theory and interviews with patients, their families, and their friends, the impact of the acute survivorship phase on the identity of patients was explored in Manitoba, Canada. Forty‐two interviews were carried out, involving 18 patients with early malignancies and 15 friends and family members. Results: The theory which evolved suggests that identity can be viewed as a construct of 3 concepts: values, social domains, and routine. Following diagnosis identity is disrupted as patients face challenges integrating the health care recipient social domain into their established routine. Patients indicated that the impact of the cancer diagnosis on their identities could have been minimized through earlier provision of the necessary information to re‐establish routine. Conclusions: The theory that emerged from this study articulates the impact of the early cancer experience on the identity of patients. It also provides a framework for predicting which interventions may improve the cancer experience. Exploring how to best provide information that helps patients re‐establish and maintain their routines after diagnosis is an important future direction.